Modelagem, simulação e análise de um cozedor contínuo de açúcar (CVP) para massa B aplicado em usinas brasileiras - Roque, Bruna Fernanda de Sousa (Universidade Federal de São Carlos, 2021)
Known as the world's largest producer of crystallized sucrose, Brazil has been investing and increasing production capacities as well as seeking for greater energy efficiency and modernization of its sugar factories. In this context, continuous crystallization processes are replacing the traditional batch vacuum pans. This work aims to model, simulate and analyze a continuous vacuum pan (CVP) of B Massecuite, by solving its mass, energy and population balances and applying kinetic models from literature. The studied CVP is a horizontal equipment of vertical tubes with twelve compartments operating under vacuum, which is similar to the equipment applied in São Martinho sugar production industry located in São Paulo state. In this way, an analysis of the industrial data was performed to define the main factors that influence the production of B Massecuite, as well as investigating the size distribution and crystal characteristics of crystal produced in each compartiment. Then, two stationary models were developed and compared for the continuous vacuum pan. The first model (Model 1) comprises CVP as a set of perfectly agitated tanks in series, while Model 2 assumes the equipment as a plug flow crystallizer. The mass, energy and population balances of the two models were performed using Microsoft Excel software applying the VBA (Visual Basic for Applications) language and a set of entry data provided by São Martinho. The results of mass and energy balance calculated via the two models were compared with the experimental B Molasses purity, while trying to adjust the population balance using experimental data from the industrial equipment, such as crystal content and average size from each one of the 12 compartments. The adjusted models were validated using a set of real data, being verified the ability to simulate the operation of the studied continuous vacuum pan and the choice by Model 2 was made, with adjusted parameters to best represent the crystal content and average size inside the equipment. The typical operating conditions of Brazilian raw sugar industries were simulated in order to understand the influence of the raw material purity on the CVP performance. The contribution of the brix value set for each compartment for productivity and quality of B Massecuite was studied and an optimal total brix curve was selected to increase production without compromising the sugar quality. Finally, a brief analysis on the operation of only one side of the CVP was performed in comparison with the operation of the 12 compartments with a lower production.
Modeling, simulation and analysis of a continuous vacuum pan (CVP) for B massecuites applied in brazilian sugar mills
Keywords: Cristalização industrial; CVP; Sacarose; Cozedor contínuo; Industrial crystallization; Sucrose; Massa B; Massecuite; Modelagem; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA